Cyclopentadienyl rhodium(III) complexes as catalysts for the insertion of phenyldiazoacetate into E−H bonds - Komarova, Alina A.; Muratov, Dmitry V.; Perekalin, Dmitry S. (Mendeleev communications, 2022)
[Display omitted] Rhodium(III) complexes catalyze the insertion of carbenoids generated from diazo compounds into E−H bonds (E = B, Si, N, but not C), although less efficiently than classical rhodium(II) carboxylates, despite formally higher oxidation state of the metal.